The study on the anti‐impact performance of the oscillating buoy with various air cushions - Ruiyin Song; Congjie Ren; Xiao Ma; Liyang Qiu; Zuan Lin (IET Renewable Power Generation, 2021)
Abstract Violent waves in ocean sometimes cause huge shocks to the oscillating buoy and cause its damage. Improving the structure of buoy is a common method to reduce the impact of water on buoy. This paper focuses on how to reduce the peak impact force and improve the survivability of oscillating buoy in ocean environment. Considering the air layer between oscillating buoy and water surface, the impact of buoy into water is taken as the research point in the paper. The corresponding mathematical model is established, and the analysis shows that the air cushion can greatly reduce the peak impact force of buoy. The finite element model of buoy is established, and the constant velocity entry of a series of buoys with different air cushion structures is calculated. First of all, the air cushions with different shapes are compared, the qualitative analysis shows that the air cushion of cylindrical shape has the excellent anti‐impact performance. Then, the air cushion structure with different volume was analysed, and the influence of different air cushion volume on the peak impact force of buoy entering water was quantified. It is concluded that the effect of reducing peak of air cushion increases with the increase of air cushion volume. Furthermore, a test bench for the impact of buoy into water was set up for experiments, and similar conclusions were obtained. Besides, it is found that the improvement of the impact resistance of air cushion slows down as the volume of air cushion increases, and there is an upper limit which is positively correlated with the impact velocity of buoy.